Identification and antifungal resistance profiling of Candida (Candidozyma) auris in a tertiary hospital in Istanbul, Türkiye - Akkaya, Yuksel; Erdin, Begum Nalca; Yilmaz, Ahmet Munir; Kilic, Ibrahim Halil; Toraman, Zulal Asci (K Faisal Spec Hosp Res Centre, 2025)
BACKGROUND: Candida (Candidozyma) auris is a high priority fungal pathogen due to its antifungal resistance and its association with increased morbidity and mortality in infected patients. OBJECTIVES: The aim of this study was to identify Candida species in clinical samples and to determine the clades and in vitro antifungal resistance of C. auris. DESIGN: Retrospective cohort SETTINGS: Single-center tertiary hospital in T & uuml;rkiye MATERIAL AND METHODS: The study was conducted in the Medical Microbiology Laboratory of & Uuml;mraniye Training and Research Hospital between December 2023 and October 2024. Fungal samples were identified using bio-M & eacute;rieux VITEK MS v.3.2 (bio-M & eacute;rieux, France) and RT-PCR. Antifungal susceptibility testing of C. auris was performed by VITEK 2 Compact AST YS08 and SYO. MAIN OUTCOME MEASURES: Identification of Candida species, invitro antifungal resistance of C. auris SAMPLE SIZE: 846 fungal isolates obtained from 746 patients were included. RESULTS: Atotal of 846 fungal isolates were identified, with C. albicans being the most common (n=440, 52%), followed by Nakaseomyces glabratus (n=124, 14.7%), C. parapsilosis (n=85, 10.1%), C. tropicalis (n=69, 8.2%) and C. auris (n=57, 6.7%). All C. auris isolates were susceptible to anidulafungin. Of these isolates, 47 (82%) were resistant to fluconazole, 34 (60%) to amphotericin B, four (7%) to caspofungin and three (5%) to micafungin. One isolate was resistant to amphotericin B, fluconazole, caspofungin and micafungin. A total of 31 (54%) isolates were resistant to amphotericin B and fluconazole. In accordance with the manufacturer's recommendations, 57 isolates were evaluated as Clade-1. CONCLUSION: C. auris infections are becoming increasingly common. In order to better understand antifungal-resistance of this pathogen, advanced methods should be used for rapid detection of clades and mutations in the FKS gene should be revealed. LIMITATIONS: Single center, whole genome sequence analysis were not performed.
Keywords: C. auris; RT-PCR; Antifungal Drug Resistance